Trends in the transformation of livestock systems in Lithuania - Juškiene V.; Juška R. (Mediterranean livestock production: uncertainties and opportunities, 2008)
Agriculture in Lithuania performs a significant social, ethno-cultural and environmental function. More than half of the country's territory is used for agricultural activities. There are favourable conditions to develop dairy and meat farming, cultivate cereals and other crops. The transition from a central planning economy to a market economy has been very complicated and hard. A very high decrease in animal production has been recorded. The study presents an analytic overview of the economic and social aspects of agricultural and livestock farming development. The diversity of farming systems, factors influencing farm diversity are described in the study. The evaluation of the changes and current trends and prospects of development of agriculture are presented in the study.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)